Duodenal perforation after gastrostomy tube replacement: Case report and literature review - Hsiao-Hui Yang; Chia-Jung Ke; Ting-Han Shih (Tzu Chi Medical Journal)
Gastrostomy is commonly used to provide long-term enteral access for patients with feeding impairment. Routine replacement is a safe procedure, but it has various complications. We present a case of nasopharyngeal cancer, who visited the emergency department for gastrostomy tube dislodgement. Diffuse abdominal pain developed 3 days after replacement of the gastrostomy tube with a temporary silicone Foley tube. Emergency diagnostic laparoscopy was performed and found tip migration and causing duodenal perforation. Tip migration and compression necrosis of mucosa were the possible mechanisms. The condition was successfully treated by emergency laparoscopic duodenorrhaphy.